ANDROID-BASED EDUCATIONAL GAME: RECOGNITION OF PAPUA ENDEMIC ANIMALS - Kristia Yuliawan; Gunawan Prayitno; Sutarto Wijono; Sri Yulianto Joko Prasetyo; Suryasatriya Trihandaru (Jurnal Teknik Informatika (Jutif), 2022)
Papua is the largest island in Indonesia; several animals are included in the endemic group. These animals are only found in certain areas and not in other areas. To study the endemic animals of Papua, children can explore them through books that display pictures of endemic animals in Papua. Children often experience difficulties learning from books taught by teachers and parents caused by children who are less enthusiastic about participating in learning. Another problem is that learning about Papua's endemic animals through books is impractical and inefficient because thick books provide a heavy burden for children to carry. Hence, children are reluctant to study them. With educational games, media is a medium that can be used by children so that it is easy to give lessons about the endemic animals of Papua. This educational game increases efficiency and effectiveness in terms of the learning process at home and school. Learning this educational game can be done anywhere at any time so that children can learn about Papua's endemic animals innovatively and efficiently. The method used in making this educational game introducing Papua's endemic animals uses the Agile Development method. Based on testing the educational game application using the black box method, it was found that this educational game was following what was expected because there were no errors found in the menu on the system, so it worked properly.